Introduction: Second-hand cultures in unsettled times. Issue 17 (9th December 2022) - Payson, Alida; Fitton, Triona; Ayres, Jennifer Lynn
Abstract : This special issue responds to a series of unfolding environmental and social crises that have contributed to an unsettled period in second-hand cultures. While these worlds have long existed as part of the informal economy, they have often been overlooked, even as a growing body of work across a range of approaches began to examine the second-hand as an integral area of cultural and social life. This special issue draws on themes and work shared at a particular moment of reflection and urgency: an interdisciplinary and international online symposium called "Second-hand Cultures in Unsettled Times", held online during the 15-16 June 2021 as the world was trying to recover from the effects of the Covid-19 pandemic . From this conference, we identify three emerging areas of study and practice in this growing field: death, waste, and the lives and "afterlives" of things, extraction and gentrification, and repair and reparation. We map the many methods and approaches to studying second-hand cultures and economies in the field. We also sketch the contours of the articles that comprise this issue around themes of waste and value, politics and change, and emotion and repair in second-hand. Finally, we outline future political orientations, questions and directions for this important area of cultural study.